Development and Validation of the Adolescents Khat Abuse Questionnaire (AKAQ) in Saudi Arabia - Anwar M Makeen (Hail Journal of Health Sciences, 2021)
Background: Khat abuse is highly prevalent in Africa and the Southern Arabian Peninsula. This study’s purpose is to examine the reliability and validity of a newly developed questionnaire on khat abuse among adolescents, which will be a useful tool for developing future studies. Methods: Approximately 157 students were recruited from three randomly selected secondary schools in the Jazan region. To assess the reliability of the questionnaire, the internal consistency and test-retest reliability of the instrument were measured. The internal consistency reliability of the instruments is represented by Cronbach’s alpha coefficient. Pearson’s correlation coefficient (R) and the Cohen’s kappa were calculated to evaluate the test-retest reliability. Results: The content of the Adolescents Khat Abuse Questionnaire (AKAQ) was validated with three constructs, and the factor analyses highlighted a three-factor structure. The questionnaire produced adequate internal consistency with Cronbach’s alpha at 0.775 for the overall scale and the three constructs with a range from 0.65 to 0.848. Conclusion: Since the AKAQ showed adequate validity and reliability, it could be a helpful tool for measuring khat abuse among adolescents, and the instrument may be applied to the Arabian population.